213k views
1 vote
Use the distributive property to simplify. (z-6)2

User Mamed
by
6.0k points

2 Answers

6 votes

Answer:


\huge\boxed{\boxed{2z-12}}

Explanation:

Hello.

Please remember that the Distributive Property states that

a(b+c)=ab+ac

Where

a, b, and c can be constants or variables.

In this case, it's flopped over:

(c+b)a=ca+ba

Use the second formula:

(z-6)2=2z-12

And we're done!

I hope it helps & have an outstanding day!

~ST2710 :)

User Nitish Pareek
by
5.3k points
1 vote

Answer:

2z-12

Explanation:

distribute 2 to the z and the 6

z times 2 = 2z

6 times 2= 12

User Natalie Perret
by
4.9k points